AN EXISTENCE AND UNIQUENESS OF THE WEAK SOLUTION OF THE DIRICHLET PROBLEM WITH THE DATA IN MORREY SPACES - Tumalun, Nicky Kurnia (PATTIMURA UNIVERSITY, 2022)
Let n-2<λ<n , f be a function in Morrey spaces L^1,λ(Ω) , and the equation Lu=f u W^1,2(Ω) be a Dirichlet problem, where Ω is a bounded open subset of R^n , n 3 , L and is a divergent elliptic operator. In this paper, we prove the existence and uniqueness of this Dirichlet problem by directly using the Lax-Milgram Lemma and the weighted estimation in Morrey spaces